Social Differentiation in Common Bottlenose Dolphins (Tursiops truncatus) that Engage in Human-Related Foraging Behaviors. - Carolyn J Kovacs; Robin M Perrtree; Tara M Cox (PLoS ONE)
Both natural and human-related foraging strategies by the common bottlenose dolphin (Tursiops truncatus) have resulted in social segregation in several areas of the world. Bottlenose dolphins near Savannah, Georgia beg at an unprecedented rate and also forage behind commercial shrimp trawlers, providing an opportunity to study the social ramifications of two human-related foraging behaviors within the same group of animals. Dolphins were photo-identified via surveys conducted throughout estuarine waterways around Savannah in the summers of 2009-2011. Mean half-weight indices (HWI) were calculated for each foraging class, and community division by modularity was used to cluster animals based on association indices. Pairs of trawler dolphins had a higher mean HWI (0.20 ± 0.07) than pairs of non-trawler dolphins (0.04 ± 0.02) or mixed pairs (0.02 ± 0.02). In contrast, pairs of beggars, non-beggars, and mixed pairs all had similar means, with HWI between 0.05-0.07. Community division by modularity produced a useful division (0.307) with 6 clusters. Clusters were predominately divided according to trawler status; however, beggars and non-beggars were mixed throughout clusters. Both the mean HWI and social clusters revealed that the social structure of common bottlenose dolphins near Savannah, Georgia was differentiated based on trawler status but not beg status. This finding may indicate that foraging in association with trawlers is a socially learned behavior, while the mechanisms for the propagation of begging are less clear. This study highlights the importance of taking into account the social parameters of a foraging behavior, such as how group size or competition for resources may affect how the behavior spreads. The positive or negative ramifications of homophily may influence whether the behaviors are exhibited by individuals within the same social clusters and should be considered in future studies examining social relationships and foraging behaviors.